Comunidade Cooperativa de Aprendizagem em Rede - Rodrigues Gonçalves, Maria Ilse (Boletim Técnico do Senac, 2006)
The possibility of “many-to-many” communication offered by cyberspace is making it possible to create virtual communities, whose translation into the educational field enables new forms of networking learning. In this article, the concepts of community and web community are explained, on certain occasions with references to presential communities and networking learning cooperative community. Organization and dynamics of cooperative groups, their advantages and difficulties are discussed, as well as the need for cooperative evaluation is highlighted and some reflections on the future are proposed.